Relationship between body fat percent and maximal oxygen uptake among young adults - Amani, Alireza; Somchit, Muhammad Nazrul; Konting, Mohd Majid; Kok, Lian Yee (Marsland Press, 2010)
The present study was conducting to examine the relationship between maximum oxygen uptake (VO2max) and body fat percent among international students in Universiti Putra Malaysia. VO2max and body fat percent are importance factors at health and sport research. Twenty six male student (26 +/- 5 years old in age and 168 +/- 5 cm in high and 73 +/- 5 kg in weight) at Universiti Putra Malaysia. Maximal were participated at this investigation. Oxygen Uptake and body fat percent have been measured by the routine protocols. At the end of this research have been shown signification and negative correlation (-0.042) between the VO2max and body fat percent. Results of this investigation show that there is negative correlation between maximum oxygen uptake and body fat percent. Increase the VO2max have been shown with decrease and improve on body composition.